Designing and Implementing IT Good Practices for Common Courts - Grabowski, Mariusz; Madej, Jan; Trąbka, Jan (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The paper presents a process for conceptualising and deploying IT (information technology) good practices formulated during the implementation of the „Education in the area of time management and cost management of judicial proceedings – case management” project (a part of Poland’s Human Capital Programme). This project was one of the components supporting the reform of the Polish judiciary and was aimed at increasing the efficiency of the judicial system by lowering costs and increasing employee skills. The paper describes all of the project phases the authors participated in their capacity as both experts and researchers. These included learning about the auto-diagnosis of 30 pilot courts, through conducting on-site visits in chosen courts, to formulating the final deployment concepts of six IT good practices implemented in a selected pool of 60 courts.